Identification of Aedes albopictus larval index thresholds in the transmission of dengue in Guangzhou, China. Issue 2 (December 2015) - Luo, Lei; Li, Xiaoning; Xiao, Xincai; Xu, Ya; Huang, Miaoling; Yang, Zhicong
ABSTRACT: Entomological indices have been used to quantitatively express vector density, but the threshold of larval indices of Aedes albopictus in dengue epidemics is still undefined. We conducted a case‐control study to identify the thresholds of Aedes albopictus larval indices in dengue epidemics. Two unit levels of analysis were used: district and street. The discriminative power of the indices was assessed by receiver operating characteristic (ROC) curves. The association between the entomologic indices and dengue transmission was further explored by a logistic regression model. At the district level, there was no significant difference in the Breteau index (BI) between districts that reported cases and those did not (t=0.164, p>0.05), but the Container index (CI) did show a significant difference (t=2.028, p<0.01). The AUC (Area Under the Curve) of BI, CI, and prediction value were 0.540, 0.630, and 0.533, respectively. Predicting at the street level, the AUC of BI, CI, and prediction values were 0.684, 0.660, and 0.685, respectively, and 0.861, 0.827, and 0.867 for outbreaks. BI=5.1, CI=5.4, or prediction value =0.491were suggested to control the epidemic efficiently with the fewest resources, where BI=4.0, CI=5.1, or PRE =0.483 were suggested to achieve effectiveness.